Answer:
The answer is x = -32
Step-by-step explanation:
In order to find the value of x, e must first distribute the 6 into the parenthesis.
6(x - 7) = 8x + 22
6x - 42 = 8x + 22
Now we will add/subtract values so that all x values are on the right and all number values are on the left.
6x - 42 = 8x + 22
-42 = 2x + 22
-64 = 2x
Now to get the final answer, divide both sides by 2.
-32 = x
Answer:
It would make it 3x
Step-by-step explanation:
4x is just a simplified version of 4 multiplied by x
4*x-x wouldn't equal 4 because you aren't following
Parentheses
Exponents
Multiplication
Division
Addition
Subtraction
(PEMDAS)
Answer:
Option (A)
Step-by-step explanation:
Given:
LM ≅ OP
MN ≅ PQ
∠M ≅ ∠P
To Prove:
ΔLMN ≅ ΔOQP
Statements Reasons
1). LM ≅ OP 1). Given
2). MN ≅ PQ 2). Given
3). ∠P ≅ ∠M 3). Given
4). ΔLNM ≅ ΔOQP 4). By the SAS postulate of congruence.
[Side - Angle - Side]
Therefore, Option (A) will be the answer.
If 7 × 2 = 14, then 14 + 14 = 28. So, 7 times 4 equals to 28. You can add 14 + 14 or multiply 7 and 4 to get your answer.